The Philippine economy no longer the East Asian exception? - Clarete, Ramon L.; Esguerra, Emmanuel F.; Hill, Hal 1948- (ISEAS Publishing, 2018)
In this volume, a leading group of scholars pose the question, has the Philippine economy rejoined the dynamic East Asian mainstream and, if so, what set of policies and priorities are required to maintain the strong economic momentum of recent years? Successive chapters address issues related to growth and poverty, infrastructure and urbanization, education, health, the environment, energy, development finance, and governance and institutions. This volume has been written with a broad audience in mind. First and foremost it is for readers in, and interested in, this fascinating and important country with a population that now exceeds 100 million people. Second, it will appeal to those in the broader development community with an interest in the analytical and policy challenges that democratic, middle-income countries face as they struggle to lift their citizens out of poverty and to achieve broad-based and environmentally sustainable growth. "[T]his rather impressive volume on the Philippine economy …[a]uthored by renowned Filipino scholars and serious observers of the Philippine economy ... is arguably the most comprehensive reference work on the economy since at least the global financial crisis in 2008–9 and will likely shape the thinking and practice of Philippine development policy in the years ahead." —Arsenio M. Balisacan Chairperson, Philippine Competition Commission Secretary of Socioeconomic Planning and Director General of NEDA, 2012–16